MEETING NEW YORK STATES FISCAL AND BUDGETARY CHALLENGES (Tufts Archival Research Center, 2007)
Draft; Confidential; Marginalia; Financial report discussing fiscal and budgetary issues in New York State. Outlines methods for New York State to better balance revenues and expenditures. Specifies increasing excise taxes for items such as cigarettes and alcohol as a way to augment revenue, as well as to help overall health.